Logistics Service Providers In Brazil: a study of geographic clustering from the perspective of logistics chain integration - Meirelles, Dimária Silva e (2014)
The aim of this study is to identify geographical clusters of logistics service provider companies in Brazil. The main contribution is a vision of these clusters based on the articulation of the various activities which make up the the logistic chain. Indicators of spatial concentration (Herfindahl index) and regional specialisations (Location Quotient) were used in order to identify geographic clustering. Information about the number of companies, their size and people working in every location in the country, were obtained through the Annual Register of Social Information (RAIS) from the Employment & Salaries Ministry and the Ministry of Labour and Employment (MTE). Due to changes in the classification of these activities in 2007, it isn't possible to carry out a broader time based analysis, which would allow us to identify the advantages of geographic clustering in a more consistent manner. We concluded that there are 922 spatial concentration of logistics service providers in Brazil. Around 41% of spatial concentration are located in the Southeast of Brazil and 33% in the South. In these regions the logistics infra-structure (roads, access to docks and airports) is more developed and also there are other logistics service chain providers.DOI: 10.12660/joscmv7n1p47-67URL: http://dx.doi.org/10.12660/joscmv7n1p47-67